INTRODUKSI TEKNOLOGI BUDIDAYA SAYURAN PEKARANGAN DILAHAN RAWA MENDUKUNG KETAHANAN PANGAN KELUARGA (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2020)
Activities of sustainable food home area in suboptimal land didn’t done as an effort to fulfill the food and nutritional needs of family and anticipate the price of food needs are increasingly expensive. The purpose of writing is to inform technological innovations that can be applied in the yard on the swampland in South Sumatera province. The utilization of vegetable cultivation in the swampland has not been carried out optimally that the yard is flooded when rainy season. The technological approach that can be done for vegetable farming in marshland is to increase the planting media and use a floating raft. The advantage of this technological innovation is that the plant is spared from the flood and simple so that it is easy to adopt, besides planting vegetables can be done several times in one season of flooding so it can increase family income. Keywords: KRPL, Technological innovations, swampland